What explains racial differences in the use of advance directives and attitudes toward hospice care? - Johnson, Kimberly S. (2008)
Cultural beliefs and values are thought to account for differences between African Americans and Whites in the use of advance directives and beliefs about hospice care. However, little data clarifies which beliefs and values explain these differences. We surveyed 205 older adults (≥ age 65) who received primary care in the Duke University Health System. The survey included five scales: Hospice Beliefs and Attitudes, Preferences for Care, Spirituality, Healthcare System Distrust, and Beliefs about Dying and Advance Care Planning. Compared to Whites, African Americans were less likely to have completed an advance directive (35.5% vs. 67.4%, P<.001) and had less favorable beliefs about hospice care (Hospice Beliefs and Attitudes Scale score, P<.001). African Americans were more likely to express discomfort discussing death, want aggressive care at the end of life, have spiritual beliefs which conflict with the goals of palliative care, and distrust the healthcare system. In multivariate analyses, none of these factors alone completely explained racial differences in either possession of an advance directive or beliefs about hospice care. However, when all of these factors were combined, race was no longer a significant predictor of either of the two outcomes. Our findings suggest that ethnicity is a marker of common cultural beliefs and values which in combination influence decision-making at the end of life. This study has implications for the design of healthcare delivery models and programs which provide culturally-sensitive end-of-life care to a growing population of ethnically diverse older adults.